Some Aspects of Teaching the Russian Language in Portugal. (2nd January 2022) - Dutta, Jayanti
ABSTRACT: This short article discusses some problems relating to the systemic-communicative method and culture- through-language studies (лингвострановедческих аспектов) aspects of teaching the Russian language outside the language environment, more specifically, in Portugal, and in accordance with this, the question of the perfect knowledge of the language of students and its use by the teacher in the classroom is discussed.